Proceedings of the 18th LACCEI International Multi-Conference for Engineering, Education, and Technology: Engineering, Integrat 2020
DOI: 10.18687/laccei2020.1.1.330
|View full text |Cite
|
Sign up to set email alerts
|

Reducción del tiempo de entrega de pedidos utilizando un modelo adaptado de gestión de almacén, SLP y Kanban aplicado en una Mype textil en Perú

Abstract: The garment manufacturing industry worldwide concentrates different critical processes, which make companies present long order delivery times, low efficiency, high process flows, line balance, etc. The present investigation proposes the reduction of the delivery time of orders using an adapted model of warehouse management, SLP and kanban applied to a textile mype in Peru, producer of garments. To do this, the diagnosis of the problem is made through a time study; It also seeks to provide support and guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…The most significant benefits of this philosophy are related to cost reduction, lead time, improved quality, and the safety and health of workers. It is developed through a set of tools and techniques and can align well with a cost-focused approach or competitive advantage strategies such as cost leadership [5],…”
Section: A Lean Manufacturing (Smed Standardized Work 5s)mentioning
confidence: 99%
“…The most significant benefits of this philosophy are related to cost reduction, lead time, improved quality, and the safety and health of workers. It is developed through a set of tools and techniques and can align well with a cost-focused approach or competitive advantage strategies such as cost leadership [5],…”
Section: A Lean Manufacturing (Smed Standardized Work 5s)mentioning
confidence: 99%
“…The Systematic Layout Planning (SLP) tool, specifically designed for plant distribution, was considered to improve the efficiency of picking times and reduce the time spent searching for products in the warehouse. [25]. In order to achieve the highest level of customer satisfaction, it is crucial to fully understand the relationship between each tool and the root problem that requires resolution, as illustrated in Figure 1.…”
Section: A Basismentioning
confidence: 99%
“…The Kanban methodology is a tool that helps in visual management and is appropriate for any type of work team, it helps to improve quality, reduce delivery time and also production costs. Works carried out demonstrate its application and it is shown that it helps the good communication between areas making use of the kanban cards, this makes that there is a reduction of times in the different activities, with the application of this technique it is possible to obtain that the delivered orders decrease in 54.39% and the number of operations go from 54 to 34 units [12]. Other scientific studies detail the adaptability of this tool and its efficiency to achieve results, support agile processes and improve working conditions [13].…”
Section: Kanban In Warehousesmentioning
confidence: 99%
“…In addition, the labels with the appropriate and necessary information for each shelf or rack, depending on the items, is a great help to keep a better record of inventory, not only because it provides accuracy, but also because it allows continuous improvement in both the performance of the operators. The delivery of orders on time is key and strategic for many companies with their customers, since reliability is compromised and guarantees a future reward, either with the same customers or with new customers [12].…”
Section: Kanban In Warehousesmentioning
confidence: 99%